Increased expression of IL‐17A and limited involvement of IL‐23 in patients with palmo‐plantar (PP) pustular psoriasis or PP pustulosis; results from a randomised controlled trial. (24th September 2013) - Bissonnette, R.; Nigen, S.; Langley, R.G.; Lynde, C.W.; Tan, J.; Fuentes‐Duculan, J.; Krueger, J.G.
Abstract Background Palmo‐plantar pustular psoriasis (PPPP) and palmo‐plantar pustulosis (PPP) are chronic skin diseases with significant impact on quality of life. Objectives The purpose of this study was to study the efficacy of ustekinumab in PPPP and PPP and gain more knowledge on the pathophysiology and the role of the interleukin‐23 (IL‐23) signalling pathway in these diseases. Methods Thirty‐three patients with either PPPP (20) or PPP (13) and seven volunteers with normal palmo‐plantar skin were recruited. Patients with PPP or PPPP were randomised (1 : 1) to receive either an anti IL‐12/IL‐23 antibody (ustekinumab 45 mg) or placebo at day 0 and week 4 with subsequent placebo cross‐over to ustekinumab at week 16. The primary endpoint was the proportion of patients randomized to ustekinumab achieving a 50% improvement in the Palmo‐Plantar Pustular Area and Severity Index (PPPASI‐50) as compared to placebo. Skin biopsies of the palms and soles of normal subjects and patients with PPP or PPPP were performed and analysed by RT‐PCR and immunohistochemistry. Results There was no statistically significant difference in the proportion of patients randomised to ustekinumab as compared to those randomised to placebo achieving PPPASI‐50 at week 16 for patients with PPPP (10%, 20%; P = 1.000) or PPP (20%, 37.5%; P = 1.000) respectively. Compared to normal subjects an 89‐fold increase in IL‐17A expression was found in palms/soles of patients with PPPP (P = 0.006) and a 190‐fold increase for patients with PPP (P = 0.051). There were no statistically significant changes in cytokine expression at week 16 in the palms and soles of patients with PPP or PPPP. Conclusion Taken together these results suggest that ustekinumab at a dose of 45 mg has limited efficacy in PPPP and PPP. IL‐17A may have a more important role than IL‐23 in patients with PPPP and PPP. Conclusions are limited by the small sample size of this study.